Implantación de contabilidad de costos y aplicación de indicadores financieros en la empresa Toscam sport de la ciudad de Loja, durante el período abril-junio del 2013 - López Maza, Yessenia Nathali (2016)
The present research with the aim of providing a contribution to the owner of the company, it has been developing as an indispensable guide for making sound decisions that guide the implementation of its goals and objectives and as a prerequisite to obtaining title of Engineers in Accounting and Auditing CPA Auditor. Based on the overall objective is considered to cost accounting system as an effective tool to promote the development and improvement of the company in all its activities by the correct distribution of the elements of the cost, getting to set the cost of each one of the items it produces, after determining all costs incurred in the preparation and knows exactly revenues, costs and expenses that generates economic activity. In terms of specific objectives shown in the first part the development of a plan and accounts manually , the different documents necessary and useful for the implementation of cost accounting that enable control of raw materials , labor and overhead costs manufacturing , to reach the objective knowledge of the financial realities of the business and therefore looking ahead . He was also necessary to use a methodological process guidance covering the collection of information necessary concepts and definitions of the subject, study of general rules of cost accounting, principles, laws and regulations of the craftsman, and tax issues meet and other laws regulate business activity.